Use of Natural Media for Early Children's Early Writing Skills - Biutris Lilianti Labulu; Ismail Marzuki; Abdul Hafid (MultiTech Publisher, 2023)
This study aims to evaluate the use of natural media in improving initial writing skills in group a aged 4-5 years. Natural material media was chosen as the focus of the research because of its potential to provide diverse sensory experiences and stimulate the development of children's motor skills. The research method used was a quasi-experiment with a control group and a treatment group. The treatment group received intervention using natural media, while the control group received conventional learning. The data collection instrument consisted of an initial writing ability test, observation of children's involvement, and interviews with teachers. The research results were analyzed using descriptive statistics and tests of differences between groups. The findings of this research indicate that the use of natural media has a positive impact on the early writing abilities of children aged 4-5 years. Children in the treatment group showed significant improvements in aspects of fine motor skills and eye-hand coordination, while the control group showed more limited improvements. The implications of the results of this research can provide recommendations to educators and parents to consider using natural media to support the development of children's early writing skills. In addition, this research can be a basis for further research in the context of using natural media for early childhood learning.